Direct quantitative 13C‐filtered 1H magnetic resonance imaging of PEGylated biomacromolecules in vivo. Issue 4 (15th April 2016) - Alvares, Rohan D. A.; Lau, Justin Y. C.; Macdonald, Peter M.; Cunningham, Charles H.; Prosser, R. Scott
Abstract : Purpose: 1 H MRI is an established diagnostic method that generally relies on detection of water. Imaging specific macromolecules is normally accomplished only indirectly through the use of paramagnetic tags, which alter the water signal in their vicinity. We demonstrate a new approach in which macromolecular constituents, such as proteins and drug delivery systems, are observed directly and quantitatively in vivo using 1 H MRI of 13 C‐labeled poly(ethylene glycol) ( 13 C‐PEG) tags. Methods: Molecular imaging of 13 C‐PEG‐labeled species was accomplished by incorporating a modified heteronuclear multiple quantum coherence filter into a gradient echo imaging sequence. We demonstrate the approach by monitoring the real‐time distribution of 13 C‐PEG and 13 C‐PEGylated albumin injected into the hind leg of a mouse. Results: Filtering the 1 H PEG signal through the directly coupled 13 C nuclei largely eliminates background water and fat signals, thus enabling the imaging of molecules using 1 H MRI. Conclusion: PEGylation is widely employed to enhance the performance of a multitude of macromolecular therapeutics and drug delivery systems, and 13 C‐filtered 1 H MRI of 13 C‐PEG thus offers the possibility of imaging and quantitating their distribution in living systems in real time. Magn Reson Med 77:1553–1561, 2017. © 2016 International Society for Magnetic Resonance in Medicine